2021
DOI: 10.1007/s43441-021-00351-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on Horizon Scanning by Citation Network Analysis and Text Mining: A Focus on Drug Development Related to T Cell Immune Response

Abstract: Certain innovative technologies applied to medical product development require novel evaluation approaches and/or regulations. Horizon scanning for such technologies will help regulators prepare, allowing earlier access to the product for patients and an improved benefit/risk ratio. This study investigates whether citation network analysis and text mining of scientific papers could be a tool for horizon scanning in the field of immunology, which has developed over a long period, and attempts to grasp the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Figure 1 gives an outline of the citation network analysis process which has been published in references ( 16 , 17 , 20 ). We converted the citation network into an unweighted network, with papers as nodes and citation relationships as links.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 gives an outline of the citation network analysis process which has been published in references ( 16 , 17 , 20 ). We converted the citation network into an unweighted network, with papers as nodes and citation relationships as links.…”
Section: Methodsmentioning
confidence: 99%
“…This study revealed that the analysis of the interdisciplinary fields is characterized by the distribution of articles in clusters of their basic technologies, which differs from AI-based medical products and immunology fields [ 12 , 13 ]. When applying horizon scanning based on the citation network analysis to an interdisciplinary research field confirming the development of the product or medical technology under consideration and evaluating not only the research trends in nonclinical studies toward clinical application but also trends in basic technologies that constitute the product or medical technology is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in our previous studies [ 12 , 13 ], citation network analysis is useful as a primary screening method for horizon scanning because the method is automated and can be easily performed even by people who do not have a high level knowledge or skill in the targeted field. This method can be used for periodical analysis for monitoring the emergence of notable innovative technologies that may require novel regulatory expertise and development of guidance.…”
Section: Discussionmentioning
confidence: 99%